The Purposefulness In Understanding Sibawayh’s Phrase Between Ibn Welad And Al-Serafi/ القصدية وأفق التأويل في فهم عبارة سيبويه بين ابن ولاد والسيرافي - Saja Mohammed Ali; Mohammed Jasim Abed; Ahmed Abdullah Hammoud (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The research aims to articulate the concept of intentionality as a cognitive and interpretive mechanism in the analysis of grammatical discourse, to reveal its impact on meaning construction and understanding of Sibawayh's texts. It starts from the hypothesis that Sibawayh's speech is an open discourse in which contextual clues interact to guide understanding. This is investigated through the study of interpretive strategies used by Ibn Waddah and Al-Sirafi, in light of their cognitive backgrounds and methodologies. The readings of Sibawayh's statements are varied due to their openness to interpretation and the differing cognitive horizons of the readers. Sibawayh's book is considered the foundational text for Arabic grammar and has served as a focal point for study, explanation, and interpretation for centuries. This research comes to examine one of the most prominent issues in interpreting this text by comparing two scholars from the 4th century AH: Ibn Waddah and Al-Sirafi. The research is based on the hypothesis that the differences between these two scholars are not merely disagreements over specific grammatical issues, but rather a fundamental divergence in their